A Rare Case of Doxycycline-Induced Autoimmune Hepatitis With Organizing Pneumonia - Alex R. Jones; Margaret Kypreos; Mark R. Pedersen (Annals of Internal Medicine: Clinical Cases)
Autoimmune hepatitis and organizing pneumonia are uncommon, yet important, manifestations of drug toxicity. We describe the case of a 67-year-old woman who presented with shortness of breath shortly after completing a course of doxycycline and was incidentally found to have a prominent hepatitis. Subsequent evaluation yielded a diagnosis of doxycycline-induced autoimmune hepatitis and organizing pneumonia. This case gives credence to including drug-induced autoimmune hepatitis and organizing pneumonia in the differential for both liver injury and respiratory failure encountered in the setting of doxycycline exposure.